Eksplorasi Kesahihan Hadis dalam Tradisi Sufi Aceh: Studi Kasus Majelis Pengkajian Tauhid dan Tasawuf Indonesia - Mawardi, Mawardi; Drajat, Amroeni; Sulidar, Sulidar (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Exploring the Authenticity of Hadith in the Sufi Tradition of Aceh: A Case Study of the Majelis Pengkajian Tauhid dan Tasawuf IndonesiaThis article explores the Majelis Pengkajian Tauhid dan Tasawuf Indonesia (MPTT-I), a Sufi group, and its critique of Hadith. Drawing on data from the book